The Oxford Book of Military Anecdotes - Edited by Hastings, Max (New York Oxford University Press, 1988)
The collection is principally British and American, with `occasional forays among the ranks of foreign armies'.
Include Bibliography and Index.
Keywords: Military art and science -- Military history -- Soldiers